Dopamine-Secreting Giant Adrenal Ganglioneuroma: Clinical and Diffusion-Weighted Magnetic Resonance Imaging Findings - A V Polat; K Aslan; H Atmaca; F Karagoz (Journal of the Belgian Society of Radiology, 2014)
We report a case of a dopamine-secreting giant primary adrenal ganglioneuroma (GN) in a 29-year-old male patient. Although the patient was clinically silent, the 24-hour urine levels of dopamine, normetanephrine, homovanillic acid and vanillyl mandelic acid were elevated. Abdominal ultrasonography and magnetic resonance imaging showed a large solid tumor with calcifications and a slightly lobular edge on the left adrenal gland. A tumor, 13 × 23 × 25 cm in size, was completely resected without morbidity. A 2-year follow-up with computed tomography showed that the postoperative course of the patient was uneventful.